Policy Controversies and Political Blame Games - Hinterleitner, Markus (Cambridge Studies in Comparative Public Policy, 2020)
In modern, policy-heavy democracies, blame games about policy controversies are commonplace. Despite their ubiquity, blame games are notoriously difficult to study. This book elevates them to the place they deserve in the study of politics and public policy. Blame games are microcosms of conflictual politics that yield unique insights into democracies under pressure. Based on an original framework and the comparison of fifteen blame games in the UK, Germany, Switzerland, and the US, it exposes the institutionalized forms of conflict management that democracies have developed to manage policy controversies. Whether failed infrastructure projects, food scandals, security issues, or flawed policy reforms, democracies manage policy controversies in an idiosyncratic manner. This book is addressed not only to researchers and students interested in political conflict in the fields of political science, public policy, public administration, and political communication, but to everyone concerned about the functioning of democracy in more conflictual times. This title is also available as Open Access on Cambridge Core.